Silica particles with immobilized protein molecules and polymer brushes. (1st January 2016) - Yang, Xiaona; Chen, Dawei; Zhao, Hanying
Graphical abstract: Abstract: In this research thermo-responsive polymer brushes and protein molecules are immobilized on the surfaces of silica particles by covalent bonds. Pyridyl disulfide functionalized silica particles are prepared by surface chemical reactions, and thiol-terminated poly(oligo(ethylene glycol) monomethyl ether methacrylate) (POEGMA) and bovine serum albumin (BSA) molecules are grafted to the silica particles by thiol–disulfide exchange reactions. X-ray photoelectron spectroscopy, thermogravimetric analysis, dynamic light scattering, confocal laser scanning microscopy, far-UV circular dichroism and transmission electron microscopy are employed to characterize the polymer/protein mixed layers on silica particles. The POEGMA brushes not only protect the protein molecules but also improve the dispersibility of the hybrid particles in aqueous solution. The activity of the immobilized BSA protein can be controlled by the thermo-responsive POEGMA brushes. At a temperature below the lower critical solution temperature (LCST) of POEGMA, BSA activity is not affected by polymer brushes; however, BSA activity decreases significantly at a temperature above the LCST of POEGMA. Statement of Significance: In this research, both protein molecules and polymer brushes were anchored to the silica particles by highly efficient thiol–disulfide exchange reaction, and their grafting density can easily be determined by UV–vis. Owing to the temperature-sensitive nature of the grafted polymer brushes, the protein molecules can be protected by the collapsed polymer brushes above the LCST, and their catalytic activity can be controlled. Moreover, the protein molecules on silica particles can be easily separated from the solution and can be reused.